Rational Design of Sulfonamide‐Based Additive Enables Stable Solid Electrolyte Interphase for Reversible Zn Metal Anode. (31st October 2022) - Huang, Cong; Huang, Fei; Zhao, Xin; Hao, Yisu; Yang, Yujie; Qian, Yang; Chang, Ge; Zhang, Yan; Tang, Qunli; Hu, Aiping; Chen, Xiaohua
Abstract: The solid electrolyte interphase (SEI)‐forming additives strategy is of great significance for improving the cycle stability of zinc (Zn) anodes. Although various additives have been reported, the relationship between their molecular structures and SEI chemistries is poorly understood. Herein, a molecular design principle for sulfonamide‐containing additives that endow Zn anodes with a robust SEI layer is proposed. The incorporation of the benzene ring and amino group (−NH2 ) leads to high adsorption energy, low lowest unoccupied molecular orbital lowest unoccupied molecular orbital (LUMO), and a small highest occupied molecular orbital‐LUMO (HOMO‐LUMO) gap, facilitating the reduction process of sulfanilamide (SA) additives. Coupled with SA/ZnSO4 electrolytes, Zn|Zn symmetric cells deliver an ultralong cycle life of 4800 h (200 days) at 2 mA cm −2 and 2 mAh cm −2 . Additionally, a high cumulative plated capacity (CPC) of 6000 mAh cm −2 and 2700 mAh cm −2 is also achieved at a capacity per cycle of 10 mAh cm −2 and 30 mAh cm −2, respectively. More importantly, the versatility of SA additives is also demonstrated in Zn‐V2 O5, Zn‐I2, and Zn‐MnO2 full cells at a low N/P ratio (the theoretical capacity ratio between the negative and positive electrode) of 5.3, 8.3, and 4.5, respectively. This molecular structure strategy provides a promising path to develop effective SEI‐forming additives. Abstract : This study provides the solid electrolyte interphase forming additive design criteria for Zn metal batteries by combined theoretical calculations and experiments. With the optimized sulfanilamide additives, Zn symmetric cells display an ultralong cycle life of 4800 h (200 days) and a high average CE of 99.3% under harsh test conditions (10 mA cm −2 and 10 mAh cm −2 ).